2015
DOI: 10.1039/c5ra06796k
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum interaction with 2,3-diphosphoglyceric acid. A computational study

Abstract: The interaction of aluminum with 2,3-diphosphoglyceric acid (2,3-DPG) is thought to be one of the strongest interactions of aluminium with a biophosphate molecule. In this article, the affinity energies for a family of Al-(2,3-DPG) complexes are calculated at the DFT level of theory. The study includes a total of 26 structures that vary from 1:1 complexes, 1:2 stoichiometry and ternary complexes with citrate, considering different coordination modes and protonation states. Our results demonstrate that in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…It is worth noting that during the optimization some proton transfer was observed from the water molecules to the closer carboxylic group (Note S1, ESI †), which are known to be due to limitations in the solvation models. 86 Our calculations demonstrate a clear increase in the aluminum binding affinity upon phosphorylation. Averaging over the three most favorable structures in each case (non-phosphorylated and phosphorylated octapeptide); we obtain an average binding free energy/enthalpy of À61.8/À69.6 kcal mol À1 for the nonphosphorylated octapeptide versus À76.3/À75.2 kcal mol À1 for the phosphorylated one.…”
Section: Binding Free Energies In Solutionmentioning
confidence: 69%
See 1 more Smart Citation
“…It is worth noting that during the optimization some proton transfer was observed from the water molecules to the closer carboxylic group (Note S1, ESI †), which are known to be due to limitations in the solvation models. 86 Our calculations demonstrate a clear increase in the aluminum binding affinity upon phosphorylation. Averaging over the three most favorable structures in each case (non-phosphorylated and phosphorylated octapeptide); we obtain an average binding free energy/enthalpy of À61.8/À69.6 kcal mol À1 for the nonphosphorylated octapeptide versus À76.3/À75.2 kcal mol À1 for the phosphorylated one.…”
Section: Binding Free Energies In Solutionmentioning
confidence: 69%
“…To answer this question, we compared our binding affinities to the ones calculated in previous studies for known strong biological chelators: citrate, the main low molecular mass chelator of aluminum in blood serum; 2,3-DPG, a chelator of aluminum in red cells, and ATP-like triphosphates. 31,86 The binding free energies/enthalpies for these chelators are: citrate (À133.0/À124.9 kcal mol À1 ) 4 2,3-DPG (À123.5/À118.9 kcal mol À1 ) 4 ATP-like triphosphates (À109.2/À108.7 kcal mol À1 ). Thus, these chelators show much larger binding affinities than the phosphorylated octapeptide.…”
Section: Biological Implicationsmentioning
confidence: 99%
“…(iv) For equimolar concentration of aluminum and G6P the formation of dinuclear complexes would be favored, through the formation of 2 : 2 complexes, rather than 2 : 1 complexes. (v) The formation of ternary compounds with citrate seems to be likely as well, as it is the case for other phosphates (2,3-DPG) 28 and other known Al-chelators (ketoglutarate, etc). 47 And nally, (vi) aluminum shows a remarkable ability to act as bridging agent to interlink G6P units (2 : 2 complexes) with structures stabilized by strong intramolecular hydrogen bonds.…”
Section: Discussionmentioning
confidence: 97%
“…The adequacy of this methodology has been proven to show good performance in the trends in binding affinity. 8,28 Nevertheless, to further conrm the adequacy of the methodology, we re-evaluated the affinity energies of the most representative complexes by single-point calculations with four different functionals: PBE0-D3BJ, TPSS-D3BJ, B97D3 and M06-2X. The trends in binding affinity are equally well described by the different functionals.…”
Section: Figmentioning
confidence: 99%
“…Interestingly, in previous studies, it was demonstrated that the formation of ternary complexes with citrate can enable a protective role with respect to some of the deleterious effects of aluminum. 27,28 In the present study, our goal is to analyze how the interaction with citrate could alter (i) the possibility of the formation of aluminum-superoxide complexes and (ii) the possibility of reducing Fe(III) to Fe(II), promoting the Fenton reaction. To do so, we evaluate the binding energies of Al(III) to superoxide and citrate, and the reaction free energy of iron reduction from Fe(III) to Fe(II) in the presence of aluminum-superoxide radical binary species and aluminum-citrate-superoxide ternary species.…”
Section: Introductionmentioning
confidence: 99%